2016
DOI: 10.1080/20477724.2016.1214350
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic utility of line probe assays for multidrug-resistant tuberculosis

Abstract: Owing to the burden of multidrug-resistant tuberculosis, molecular techniques have been approved by the WHO for the rapid diagnosis of the same. The objectives of this prospective, diagnostic study, conducted at Christian Medical College, a tertiary care center in South India, were to compare the performance of line probe assay (GenoTypeMTBDRplus) with culture, as well as the Xpert MTB/Rif assay on sputum samples. Ninety-one consecutive suspects of multidrug-resistant pulmonary tuberculosis patients from Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
3
15
0
Order By: Relevance
“…Ninan et al . (2016) reported similar sensitivity rates (67%) in smear negative samples for LPA in their study as observed herein with SN-CP specimens, with our LPA also showing a sensitivity of 66.67% 22 . However our LPA sensitivity was a little lower than that reported by Meaza et al .…”
Section: Discussionsupporting
confidence: 86%
“…Ninan et al . (2016) reported similar sensitivity rates (67%) in smear negative samples for LPA in their study as observed herein with SN-CP specimens, with our LPA also showing a sensitivity of 66.67% 22 . However our LPA sensitivity was a little lower than that reported by Meaza et al .…”
Section: Discussionsupporting
confidence: 86%
“…The aim of our study was to evaluate the utility of the latest version of LPA for the diagnosis of sputum smear-negative PTB patients. Almost similar sensitivity (66.7%) with high specificity (92.3%) was observed in a study conducted by Ninan et al [ 15 ] for the detection of MTB with MGIT-960 culture as reference standard. Another study conducted by Meaza et al [ 16 ] showed both higher sensitivity (77.8%) and specificity (97.9%).…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, in our study, we used larger volumes of decontaminated sputum sample (1 mL) as compared to that recommended by the manufacturer (0.5 mL). This might have resulted in higher detection rates of MTB by LPA from the previous studies conducted by Ninan et al [ 15 ] and Meaza et al [ 16 ]; however, it warrants validation in future studies and the possible re-evaluation of the assay’s methodology.…”
Section: Discussionmentioning
confidence: 96%
“…The detection of dead bacilli by molecular technique may have resulted to false positive results. Hence, when a new test is assayed against culturing method as a reference standard, it can show false positive results 14,21. Two cases were reported as false negative by LPA method, which these cases were reported “very low” by GeneXpert MTB/RIF and were grown in culture.…”
Section: Discussionmentioning
confidence: 99%
“…This method also known as line probe assay (LPA) is based on polymerase chain reaction (PCR) and hybridization assay. Specific gene for MTB complex, mutations in rpoB for RIF resistance, katG for high-level INH resistance, and inhA for low-level INH resistance are detected directly from clinical samples by LPA method 14. However, because of strain diversity and various types of mutations in drug-resistant MTB, LPA assay needs to be studied particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%